(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the labeling and classification of breads, biscuits and toasts declared as wholegrain and to compare them. The cross-sectional and descriptive study was carried in Uberaba, in 2016. Products sold in five supermarkets were classified as processed or ultra-processed according to the NOVA system, which considers the industrial processing employed. The Pan American Health Organization Nutritional Profile Model was used to classify products with excessive amounts of critical nutrients. The products were evaluated for the carbohydrate:fiber ratio recommended by the American Heart Association. A total of 147 products were analyzed: 99 biscuits, 36 breads and 12 toasts. The average number of ingredients in the formulations was 17.3±5.4, so that 100% of the products were classified as ultra-processed. The majority, 64.6%, did not present wholegrain flour as the first ingredient. The declaration of supplementary nutritional information on dietary fiber was present in 49% of the products and 100% complied with the mandatory requirements. Despite that, 53.7% presented excessive levels of sodium and 22.4% and 56.5% had excessive levels of total and saturated fat, respectively. For the criterion of carbohydrate:fiber ratio, 38.7% had a ratio of ≥10:1, mainly biscuits, which is undesirable. All biscuits, breads and toasts sold as "wholegrain" were ultra-processed, with excessive sodium content (breads and toast in general) and fats (most biscuits). Wholegrain flours only accounted for 35.4% of the products and half of the toasts, and most of the biscuits (66.7%) could not be considered a source of fiber.